P16 Radial ebus biopsy with guide sheath for peripheral pulmonary lesions. (15th November 2016) - Srikanthan, K; Drouot, C; Sukumaran, B; Johnson, V; Walshaw, M; Mohan, K
Abstract : Introduction: The aim of lung cancer screening programs is the detection of early lung cancer, which may appear as small peripheral pulmonary lesion (PPL). Although radial EBUS guided biopsy is recommended by NICE to obtain tissue diagnosis in PPL which cannot be seen by conventional bronchoscopy, there is a paucity of published data within the UK regarding this technique. We looked at our 4-year radial EBUS results at our tertiary centre. Methods: We reviewed 71 consecutive patients who underwent radial EBUS guided biopsy for investigation of a PPL, performed using a guide sheath (K201 or K203) by a consultant operator assisted by a respiratory trainee. We assessed the diagnostic rate, yield from sampling techniques (biopsy vs brushings), whether the diagnosis correlated with other procedures/management, and any complications. Results: Mean patient age was 70 years (range 44–89), 38 female, and 41 (58%) had undergone 1 or more unsuccessful investigations at their local hospital. We were able to visualise the lesion by ultrasound leading to subsequent sampling in 62/71 (87 %) patients. A diagnosis of malignancy was confirmed in 41/62 (66%) patients. Of the 21 biopsies which did not demonstrate malignancy, 11 were subsequently shown to have cancer (false negatives–pathological diagnosis by other methods or clinical-radiological diagnosis or awaiting follow up) but were 10 true negative (resolution or 2 year stability on CT scan). The yield for malignancy was superior with brushings (88%) compared to biopsy (73%). The overall sensitivity for cancer was 72% (N = 71, whole cohort) and 82% (N = 62, lesion was visualised by ultrasound) respectively. Two patients developed a pneumothorax which did not require intervention. Conclusions: Radial EBUS is a safe and effective technique in obtaining tissue diagnosis in PPL not amenable to other biopsy methods. We visualised the lesion in 87% of patients and our diagnostic yield for malignancy is similar to current standards. Radial EBUS should take a more prominent role in diagnostic pathways for PPL within the UK, particularly in the context of future lung cancer screening programmes.